Obesity prevalence, nutritional status, and physical activity levels in Turkish adults during the COVID-19 pandemic - Karaca Çelik, Kezban Esen; Morales-Suárez-Varela, María; Uçar, Nazlı; Soriano, Jose M.; İnce Palamutoğlu, Merve; Baş, Murat; Toprak, Dilek; Hajhamidiasl, Ladan; Erol Doğan, Özge; Doğan, Mert (Frontiers in Nutrition, 2024)
Background: Although nutritional status is influenced by multidimensional aspects encompassing physical factors, there is limited research on this complex relationship. Objectives: This study aimed to examine the interaction between physical activity level indicators and the nutritional status of adults in Türkiye. Methods: A total of 3,970 individuals aged 18 years or older, residing in Afyonkarahisar (Türkiye), participated in this study. Data were obtained through face-to-face interviews with a questionnaire, using simple random sampling among adults. One-day food consumption was recorded using a 24hour dietary recall (24HDR). Physical activity levels were assessed using the International Physical Activity Questionnaire (IPAQ).Results: This study comprised 3,970 participants: 2,087 (52.57%) men and 1,883 (47.42%) women. Among them, 32.64% smoked cigarettes, and 8.72% consumed alcohol. About 40% of adults were overweight, and 16.33% were obese. All participants had inadequate intake levels of potassium, calcium, and iron when compared to the recommended amounts. Physical activity levels showed a weak positive correlation with dietary energy, carbohydrates, protein, fat, and cholesterol, and a weak negative correlation with age, waist-to-hip ratio, and BMI of participants.This study provides insights into the importance of addressing both physical activity and nutritional status. It was found that the weekly duration of physical activity for women was lower than for men. As a result of the nutritional status evaluation, it was found that the daily energy intake of men was higher than that of women.